REPRESENTATION OF PATRIOTIC VALUES IN THE SONG LYRICS OF FALASTHIN BILADIY BY HUMOOD AL KHUDEER: A ROLAND BARTHES SEMIOTIC ANALYSIS - Rifki Mustofa; Dien Nur Chotimah; Mellinda Raswari Jambak; Muhammad Aslam Islami (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2025)
The song Falasthin Biladiy by Humood AlKhudher emerged from the context of the Palestinian people's resistance in their struggle for independence and national identity. This study aims to examine how patriotic values are represented in the lyrics of the song, using Roland Barthes’ semiotic approach, focusing on two levels of meaning is denotation and connotation. The study employs a qualitative descriptive method with the Miles and Huberman data analysis model, which includes data condensation, data presentation, drawing conclusion and verification. The findings reveal that the song’s lyrics successfully represent eight forms of patriotic values, including Love of country, Solidarity of unity, Willing to sacrifice, the spirit of resistance, among others. The lyrics function as a medium for expressing collective awareness and constructing national identity through powerful narrative and poetic symbolism. This research is centered on textual analysis without directly examining the listeners’ responses or reception. Therefore, this study contributes to the field of semiotics and cultural analysis, particularly in understanding how contemporary Arabic music texts serve as symbolic communication media within political and national discourse.